Expanded insecticide catabolic activity gained by a single nucleotide substitution in a bacterial carbamate hydrolase gene - Başak Öztürk; Maarten Ghequire; Thi Phi Oanh Nguyen; René De Mot; Ruddy Wattiez; Dirk Springael (Environmental Microbiology, 2016)
Summary Carbofuran‐mineralizing strain Novosphingobium sp. KN65.2 produces the CfdJ enzyme that converts the N ‐methylcarbamate insecticide to carbofuran phenol. Purified CfdJ shows a remarkably low K M towards carbofuran. Together with the carbaryl hydrolase CehA of Rhizobium sp. strain AC100, CfdJ represents a new protein family with several uncharacterized bacterial members outside the proteobacteria. Although both enzymes differ by only four amino acids, CehA does not recognize carbofuran as a substrate whereas CfdJ also hydrolyzes carbaryl. None of the CfdJ amino acids that differ from CehA were shown to be silent regarding carbofuran hydrolytic activity but one particular amino acid substitution, i.e., L152 to F152, proved crucial. CfdJ is more efficient in degrading methylcarbamate pesticides with an aromatic side chain whereas CehA is more efficient in degrading the oxime carbamate nematicide oxamyl. The presence of common flanking sequences suggest that the cfdJ gene is located on a remnant of the mobile genetic element Tn ceh carrying cehA . Our results suggest that these enzymes can be acquired through horizontal gene transfer and can evolve to degrade new carbamate substrates by limited amino acid substitutions. We demonstrate that a carbaryl hydrolase can gain the additional capacity to degrade carbofuran by a single nucleotide transversion.